DLC 코팅한 Fe-3.0%Ni-0.7%Cr-1.4%Mn-X강의 표면특성평가 - 장재철(Jaecheol Jang); 김송희(Song-Hee Kim) (Biuletyn Uniejowski, 2014)
The various surface treated conditions of Fe-3.0%Ni-0.7%Cr-1.4%Mn-X steel such as as-received, ion nitriding, DLC coated, DLC coated after nitriding for 3 hrs and 6 hrs were investigated to evaluate the beneficial effect for plastic mold steel. Micro Vickers hardness tester was used to estimate nitriding depth from the hardness profile and to measure hardness on the surface. Elastic modulus and residual stress were measured by a nanoindentator. Scratch test and SP (small ball punch test) were utilized to assess the adhesive strength of DLC coating. The depth of nitriding layer was measured as $50μm$ for the condition of 3 hrs nitriding and $90μm$ for that of 6 hrs nitriding. Hardness, elastic modulus, residual stress of DLC coating were 20.37 GPa, 162.78 GPa and -1456 MPa respectively. Residual stress on the surface of DLC coating after nitriding could increase to -3914 MPa by introducing nitriding before DLC coating. During the 'Ball-On-Disc' test ${γ}^{′}$ particles pulled out from the surface of nitrized layer tend to enhance abrasive wear mode since the fraction of ${γ}^{′}$ (Fe4N) in ion-nitrized layer is known to increases with nitriding time. Thus the specific wear rate of the nitriding layer increased. Comparing with nitriding the specific wear rate in work piece disc as well as ball decreased prominently in DLC coating due to the remarkable reduction in friction coefficient.